Digital health technologies for improving the management of people with chronic obstructive pulmonary disease - Park, Hye Yun; Kong, Sunga; Lee, Mangyeong; Ryu, Hyein; Hamakawa, Yoko; Luppi, Fabrizio; Leung, Janice M. (Frontiers in Digital Health, 2025)
Advances made in digital health in recent years have the potential to improve the care of patients living with chronic obstructive pulmonary disease (COPD) for whom substantial disability still exists. In particular, telehealth and telerehabilitation programs, wearable devices, and apps have been studied as novel methods of providing care to COPD patients who may have limited access to clinical centers or who may benefit from an increased level of monitoring. Many of these interventions gained traction during the COVID-19 pandemic when mandated social isolation required the rapid implementation of remote care models. While these digital health interventions have since demonstrated promise in delivering care to otherwise isolated communities, the ongoing need for more evidence proving their positive impact on important clinical outcomes remains a barrier to their full implementation. How to best integrate digital health solutions into existing care models requires greater consideration of the technological, financial, and labor demands such solutions may entail.